2020
DOI: 10.1038/s41388-020-1167-x
|View full text |Cite
|
Sign up to set email alerts
|

The multifunctional protein PACS-1 is required for HDAC2- and HDAC3-dependent chromatin maturation and genomic stability

Abstract: Phosphofurin acidic cluster sorting protein-1 (PACS-1) is a multifunctional membrane traffic regulator that plays important roles in organ homeostasis and disease. In this study, we elucidate a novel nuclear function for PACS-1 in maintaining chromosomal integrity. PACS-1 progressively accumulates in the nucleus during cell cycle progression, where it interacts with class I histone deacetylases 2 and 3 (HDAC2 and HDAC3) to regulate chromatin dynamics by maintaining the acetylation status of histones. PACS-1 kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 52 publications
(51 reference statements)
0
27
0
Order By: Relevance
“…Thus, we elected not to exclude discordant expression as these trends may also harbour therapeutic targets and reveal further insight into altered gene expression between low-and high-grade meningioma. Among those transcripts/proteins displaying the strongest discordant expression with high protein but low transcript LFC in grade III tumours were the Na + /HCO 3 co-transporter SLC4A4, previously shown to contribute to the proliferation, migration and invasion of a breast cancer cell line [58], and the phosphofurin acidic cluster sorting protein-1, PACS1, recently revealed to function in the nucleus as an epigenetic regulator to promote oncogenic replication and progression [58,59]. To further investigate this discordant trend, we hypothesised that tumour vasculature may play a role in delivering proteins that are not upregulated on the transcript level in the tissue itself, to the tumour tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we elected not to exclude discordant expression as these trends may also harbour therapeutic targets and reveal further insight into altered gene expression between low-and high-grade meningioma. Among those transcripts/proteins displaying the strongest discordant expression with high protein but low transcript LFC in grade III tumours were the Na + /HCO 3 co-transporter SLC4A4, previously shown to contribute to the proliferation, migration and invasion of a breast cancer cell line [58], and the phosphofurin acidic cluster sorting protein-1, PACS1, recently revealed to function in the nucleus as an epigenetic regulator to promote oncogenic replication and progression [58,59]. To further investigate this discordant trend, we hypothesised that tumour vasculature may play a role in delivering proteins that are not upregulated on the transcript level in the tissue itself, to the tumour tissue.…”
Section: Discussionmentioning
confidence: 99%
“…While the involvement of hsa-miR-34a in cervical and other human tumors has been well established, the role of hsa-miR-449a in cancer is not well defined (25)(26)(27)(28)(29)(30)(31) . A recent report has shown that PACS-1 has a role in epigenetic regulation of gene expression (32). However, regulation of PACS-1 is not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…We next hypothesized that PACS‐1 might shuttle cargo to and from the nucleus via its own nuclear trafficking. As PACS‐1 accumulates in cell nuclei during the S phase of the cell cycle to maintain chromosomal stability by regulating HDAC2 and HDAC3, we searched for potential nuclear substrates of PACS‐1 that may be involved in this process [11]. It has been previously demonstrated that a complex between HDAC2 and the polypyrimidine tract‐binding protein 1 (PTBP1) influences the interplay of histone deacetylation and RNA splicing [48,49].…”
Section: Resultsmentioning
confidence: 99%
“…PACS‐1‐WT‐GFP [5,11] and PACS‐1‐WT‐FLAG (DYKDDDDK) [16] were previously described. pDONR223‐XPO1‐WT was a gift from Jesse Boehm, William Hahn, and David Root (Addgene plasmid #81812) [17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation